2009
DOI: 10.1038/nphys1218
|View full text |Cite
|
Sign up to set email alerts
|

Measuring photon bunching at ultrashort timescale by two-photon absorption in semiconductors

Abstract: Photon beams exhibit temporal correlations that are characteristics of their emission mechanism. For instance, photons issued from incoherent sources tend to be detected in bunches. This striking 'bunching' behaviour has been observed in the seminal experiment by Hanbury-Brown and Twiss (HBT) in the fifties, who measured the time of arrival of partially coherent photons on two separate photon-counting modules 1. Since then, HBT interferometry has become a widespread technique to study photon correlations down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
107
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(107 citation statements)
references
References 31 publications
0
107
0
Order By: Relevance
“…These photons are distinguishable for the detection system based on photoelectric effect and no second-order interference pattern can be observed. The time measurement uncertainty of two-photon absorption is at femtosecond range [46]. Photons with frequency difference less than 10 6 GHz are indistinguishable for the detection system.…”
Section: Discussionmentioning
confidence: 98%
“…These photons are distinguishable for the detection system based on photoelectric effect and no second-order interference pattern can be observed. The time measurement uncertainty of two-photon absorption is at femtosecond range [46]. Photons with frequency difference less than 10 6 GHz are indistinguishable for the detection system.…”
Section: Discussionmentioning
confidence: 98%
“…They showed that the coherence area was related to the angular size of the radiation source [7]. Interestingly, a similar effect also appears in the temporal domain [8], i.e., for thermal-like sources, the photons appear correlated for time instants shorter than the inverse of the bandwidth of the source. On the contrary, for fermions [9] and photons showing sub-Poisson statistics [10], the effect is just the opposite.…”
mentioning
confidence: 99%
“…However, the measurement of second-and higher-order coherence functions of broadband light sources is especially challenging since, due to their large bandwidths, ultrafast (typically in the femtosecond regime) detection schemes are needed [13]. In fact, it was not until very recently that the second-order coherence properties of true thermal photons were experimentally observed [8].…”
mentioning
confidence: 99%
“…While usually the spectral and temporal properties of light fields are considered to be of highest interest, especially for studies of coherence properties, the quantum statistics of light fields matter as well [1][2][3]. During the last few years, experimental techniques aimed at studies of photon number statistics have improved significantly [4][5][6][7][8][9][10][11], as has the fundamental understanding of photon number statistics [12]. Recently, some emphasis has also been placed upon using the quantum statistics of the excitation light field as a degree of freedom in spectroscopy [13][14][15][16] and quantum-optical spectroscopy has recently been applied to reveal significant physical effects and new quasiparticles, such as dropletons [17,18].…”
mentioning
confidence: 99%